Evaluation of SARS-CoV-2 RNA quantification by RT-LAMP compared to RT-qPCR1Abbreviations: COVID-19, coronavirus disease 2019; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2; RT-LAMP, reverse transcription loop-mediated isothermal amplification; RT-qPCR, reverse transcription quantitative PCR, MERS, Middle East respiratory syndrome, SARS, severe acute respiratory syndrome. Issue 7 (July 2021) - Minami, Kenta; Masutani, Ryota; Suzuki, Youichi; Kubota, Meri; Osaka, Naofumi; Nakanishi, Toyofumi; Nakano, Takashi; Ukimura, Akira
Abstract: Introduction: Coronavirus disease 2019 (COVID-19) is a global pandemic caused by a novel virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The viral load of SARS-CoV-2 is associated with mortality in COVID-19 patients. Measurement of viral load requires the use of reverse transcription quantitative PCR (RT-qPCR), which in turn requires advanced equipment and techniques. In this study, we aimed to evaluate the viral load measurement using reverse transcription loop-mediated isothermal amplification (RT-LAMP), which is a simpler procedure compared to RT-qPCR. Materials and methods: RNA was extracted by using the QIAamp Viral RNA Mini Kit. The RT-LAMP assay was performed by using the Loopamp® 2019-SARS-CoV-2 detection reagent kit and 10-fold serial dilutions of known viral load RT-LAMP were used to measure Tt, which is the time until the turbidity exceeds the threshold. Based on the relationship between viral load and Tt, the linearity and detection sensitivity of the calibration curve were evaluated. In addition, 117 clinical specimens were measured, and RT-qPCR and RT-LAMP assay results were compared. Results: The dilution linearity of the calibration curve was maintained at five orders of magnitude 1.0× 10 6 to 1.0 × 10 1 copies/μL, and was confirmed to be detectable down to 1.0 × 10 0 copies/μL. The limit of quantification of RNA extracted from clinical specimens using RT-LAMP correlated well with that obtained using RT-qPCR ( r 2  = 0.930). Conclusion: The findings indicate that RT-LAMP is an effective method to determine the viral load of SARS-CoV-2.